Research Progress on Activation and Modification Techniques of Humic Acid - Sun, Yutong; Xia, Liheng (International Journal of Agriculture and Food Sciences Research, 2024)
Humic acid is a naturally occurring organic substance found extensively in soils, coal, and peat, characterized by a complex molecular structure with abundant functional groups. Recent advancements in activation and modification techniques, such as oxidation, alkalization, and biological modification, have significantly enhanced the solubility, stability, and bioactivity of humic acid. These techniques have broadened its applications in agricultural productivity, soil improvement, and environmental protection. This review summarizes the principles and effects of various activation and modification techniques and discusses their roles in agriculture and environmental management. It also highlights the current achievements and limitations in the field, as well as potential directions for future research on humic acid activation and modification.